The Revenue Allocation Framework And Local Government Systems In Kano And Sokoto, Nigeria - Koko, Muhammad Nuruddeen (2023)
Nigeria’s federation has been evolving for many decades. From its inception, the federal system had been sloppy, battered, contested, and conflict-ridden. These have been attributed to a lack of mutual trust among the diverse groups within the federation and, most importantly, a lack of consensus on the revenue allocation framework. Thus, the search for an appropriate financing system took centre stage throughout the country’s existence. However, the return to civil rule in 1999 once more ignited the hope for a functional and appropriate federal system that would set the country’s treacherous experiences straight. Alas, the period further witnessed the severe weakening of various governance structures, particularly the local governments, which were adjudged to be the closest unit of authority to the citizens. In view of these, the study examined how the existing revenue allocation framework affects the local government system in Kano and Sokoto states of Nigeria, given the distressing situation and structural problems bedevilling local governments. The study adopted the political settlement approach, complemented by comparative historical analysis, to develop key contributions to Nigeria’s intergovernmental fiscal relations and governance.